GENETIC DISSIMILARITY IN JABUTICABA (Plinia peruviana (poir.) govaerts) IN MUNICIPALITY SÃO MATEUS, NORTH OF STATE ESPÍRITO SANTO, BRAZIL (Revista Ifes Ciência, 2023)
Jabuticaba (Plinia peruviana (Poir.) Govaerts) is a plant rich in compounds that are very useful in industry. Its fruits are the basis for a range of food and pharmaceutical products. Due to the great potential of this species, information about genetic structure of these plants allows us to understand factors linked to quality, in addition to guiding crosses to improve this species for commercial purposes. Thus, we sought to understand the pattern of genetic diversity of jabuticaba found in the municipality São Mateus, north region of Espírito Santo State, Brazil, using ISSR markers. The results of the dissimilarity values, obtained by the Jaccard index, grouped the 19 accessions studied into five groups. The pair of accessions 10 and 19 showed the highest dissimilarity value, being indicated for further studies with specific markers, to infer the maximum heterozygosity, and possible potential for exploitation of heterosis. Accessions 16 and 18 had a lower dissimilarity value, being promising in introgression and gene association studies, due to the narrow genetic basis between the materials. Accessions 1, 4, 12, and 15 are the most divergent and can be indicated for random artificial crossings.